AUDIOBOOKS AS A MEDIUM TO ENHANCE EFL STUDENTS’ READING COMPREHENSION - Datumusu, Nazirah Amalia T. (Universitas PGRI Sumatera Barat, 2025)
Audiobooks offer both auditory and visual input that support students' reading. Although widely discussed, their impact on Indonesian EFL students’ reading comprehension remains underexplored. This study investigates whether audiobooks can enhancereading comprehension. A quasi-experimental design involved 66 students, divided into an experimental group (n=32) taught with audiobooks and a control group (n=34) taught with printed texts. Both groups were selected using purposive sampling. Data from pre-test and post-test were analyzed using an independent samples t-test. Results show the experimental group had a higher post-test mean score (78.28) than the control group (67.18). A Sig. (2-tailed) value of 0.001, which is less than the p-value of 0.05, indicating a statistically significant difference between the two groups. These findings confirm audiobooks are effective for enhancing reading comprehension. This study adds insight by applying audiobooks in an Indonesian EFL classroom and highlights their potential to improve reading instruction quality. The implication for teaching practice is the potential of audiobooks to enhance the quality of reading instruction.